Modified Ultra Wideband (UWB) Antipodal Vivaldi Antenna for 5 - Subuh Pramono; Budi Basuki S.; Tommi Hariyadi (Institute of Advanced Engineering and Science, 2018)
This paper presents a half triangular Comb-shaped slits edge Antipodal Vivaldi Antenna (Comb-AVA) as compared to the conventional Antipodal Vivaldi Antenna (AVA) design. This proposed antenna covers 20-40 GHz spectrum. This Comb-AVA antenna is designed for the 5G application which is addressed to cover a dualband 28/38 GHz frequencies. A half triangular comb-shaped slits edge structure is employed to investigate its effects on antenna parameters. This proposed Comb-AVA occupies a 25x8 mm2 of FR 4 substrate (???????? = 4.4, tan δ=0.02, thinkness 1.6 mm). It has impedance bandwidth (S11≤-10 dB) along 20-40 GHz spectrum and fractional bandwidth (FBW) ≥0.5. It means that the bandwidth is categorized as ultra wideband (UWB). In addition, there is 11 dB refinement of return loss in the CombAVA design at 38 GHz frequency. VSWR value is in range of 1.054 to 1.396. This proposed antena also has a wider angular width (3 dB) than the AVA. Higher directivity and gain is generated by Comb-AVA at 28 GHz. This proposed antenna has good performances and suitable for 5G application.